Pravljične ure z zgodovinsko tematiko in slovenske splošne knjižnice - Ugovšek, Mateja (Knjižnica, 2010)
The article presents a new approach to story hours in public libraries being also an early learning opportunity for children. In this way, for example, preschool children may raise their interest in history. One of the tasks of a public library is to offer story hours for children. At the same time it can successfully promote its services and take the opportunity to recruit new members. A story hour dealing with a historical theme was offered at the Public Library of Mozirje and was well accepted by children and their parents. A survey gathering statistical data on story hours in Slovenian public libraries was carried out and 25 libraries responded to the electronic questionnaire. The results show that story hours are mostly offered four times a month and usually held by women having university education. However, historical story time themes are selected very rarely.
Keywords: bibliopedagoško delo; pravljične ure; zgodovinska tematika; splošne knjižnice; zgodnje učenje